Machiavelli an amoral with moral elements: An approach to histhought on ethics - Miranda Fonseca, Héctor Eduardo (2014)
This paper tries to explain the broad outlines of the thought of Nicolás Maquiavelo, in order to establish his amoral thinking and how through categories of analysis tries to explain his thinking around policy and the recognition of the new stage in Europe, is beginning to take shape with the emergence of the modern State, and you want to frame this theoretica l approach to the end, discovered at that thought, in overt form are ethical elements, which are not discovered in their own thinking, but in his behavior as a person, and by the historical moment that you live in Italy.